Angular Distribution of Ion Products in the Double Photoionization of Propylene Oxide - Falcinelli, Stefano; Rosi, Marzio; Pirani, Fernando; Bassi, Davide; Alagia, Michele; Schio, Luca; Richter, Robert; Stranges, Stefano; Balucani, Nadia; Lorent, Vincent; Vecchiocattivi, Franco (Frontiers in Chemistry, 2019)
A photoelectron-photoion-photoion coincidence technique, using an ion imaging detector and tunable synchrotron radiation in the 18.0 – 37.0 eV photon energy range, inducing the ejection of molecular valence electrons, has been applied to study the double ionization of the propylene oxide, a simple prototype chiral molecule. The experiment performed at the Elettra Synchrotron Facility (Trieste, Italy) allowed to determine angular distributions for ions produced by the two-body dissociation reactions following the Coulomb explosion of the intermediate (C3H6O)2+ molecular dication. The analysis of the coincidence spectra recorded at different photon energies was done in order to determine the dependence of the β anisotropy parameter on the photon energy for the investigated two-body fragmentation channels. In particular, the reaction leading to CH3+ + C2H3O+ appears to be characterized by an increase of β, from β ≈ 0.00 up to β = 0.59, as the photon energy increases from 29.7 to 37.0 eV, respectively. This new observation confirms that the dissociation channel producing CH3+ and C2H3O+ final ions can occur with two different microscopic mechanisms as already indicated by the bimodality obtained in the kinetic energy released distributions as a function of the photon energy in a recent study. Energetic considerations suggest that experimental data are compatible with the formation of two different stable isomers of C2H3O+: acetyl and oxiranyl cations. These new experimental data are inherently relevant and are mandatory information for further experimental and theoretical investigations involving oriented chiral molecules and linearly or circularly polarized radiation. This work is in progress in our laboratory.